A Radical Treatment for Insulin Pricing - Dafny, Leemore S. (The New England journal of medicine, 2022)
A Radical Treatment for Insulin PricingA private, nonprofit company recently announced that it intends to bypass the traditional supply chain and sell interchangeable biosimilar insulin products at substantially reduced prices.